Transformational and transactional leadership styles in enhancing nurse educator’s job satisfaction: an integrative analysis of conventional and Islamic approaches - Moey, Soo Foon; Hashi, Abdurezak Abdulahi (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
As nursing education increased its’ complexity, leadership styles employed in these nursing training institutions played a crucial role in achieving nurse educators’ job satisfaction. As such, this study intends to elicit attributes and practices of nursing academic leaders’ transformational and transactional leadership styles in enhancing the job satisfaction of nurse educators. The qualitative method used for the study was based on the phenomenological approach to gather an in-depth understanding of human behaviour through interview, documents and observations. Purposive sampling was undertaken in selecting nine nurse educators from three nursing colleges from Johor and Melaka. Data from the interview were summarized in answering nurse educators' job satisfaction and perceived leadership styles and practices of nursing academic leaders. The responses from the verbatim transcriptions were analysed using the software Atlas Ti. The strong relationship between nursing academic leadership styles and nurse educators’ job satisfaction suggested that the academic nursing transformational leadership style played a prominent role on subordinates’ job satisfaction and that nursing academic leaders’ transformational leadership practices and attributes had the ability to encourage subordinates to achieve more than what they planned. Transactional leadership practised by the nursing academic leaders indicated a weak link to subordinates’ job satisfaction as the leaders’ emphasis on payoffs for performance and corrective actions were not as acceptable to that transformational leadership attributes practised by the leaders. The study uncovered effective leadership was enacted via engaging leadership where the leader enabled the development of an organization modelled by a culture of integrity, transparency, accessibility and genuine valuing of others and that their contributions were concerned for the development and well-being of others. In fact, moral attributes like integrity, trustworthiness and commitment to work as well as decision making styles of leaders such as being consultative leader are among the basic Islamic teachings on establishing worthy social order.